Determinação de fármacos antidiabéticos orais em plasma humano empregando microextração em sorvente empacotado e cromatografia líquida de alta eficiência - Iara Maíra de Oliveira Viana (2014)
Diabetes mellitus is a chronic disease characterized by the insufficient production of insulin or by the inability of the body to effectively use all the insulin which is produced by the pancreas. The initial treatment of the mostly common type 2 diabetes mellitus consists in changes in lifestyle, mainly in diet and physical exercises. However, due to the progressive feature of the disease the prescription of oral drugs to control the glycemia is a common practice. The sulfonylureas drugs have been largely used for the glycemic control. In this study, a simple method was developed and validated using microextraction in packed sorbent and high performance liquid chromatography with ultraviolet detection for the simultaneous determination of three oral antidiabetic drugs of the class of sulfonylureas (chlorpropamide, gliclazide e glimepiride) in human plasma. Glibenclamide, another sulfonylurea, was used as internal standard. A fractional factorial planning and a complete factorial planning were applied to evaluate the parameters that affect the stages of extraction and desorption, respectively. Every parameter of the extraction stage (pH, sample volume, sample dilution and number of aspiration/ejection cycles) and of the desorption stage (acetonitrile percentage in the elution solvent and the number of cycles of aspiration of the elution solvent through the cartridge) were statistically significant (p<0.05) when the recovery was used as the measurement. The developed method allowed the use of small sample and solvent volumes. The performed experimental planning helped the rational choice of the best conditions for each parameter in order to obtain satisfactory recovery and sensitivity. The fast and efficient separation of the drugs was possible with the use of a fused-core particles column (run time of 2.2 min). This method was validated showing selectivity, precision, accuracy and linearity in the linear ranges of 1.0-50.0 µg mL-1 for chlorpropamide, 1.0-10.0 µg mL-1 for gliclazide and 0.1-1.0 µg mL-1 for glimepiride. Finally, the validated method was applied for the analysis of human plasma samples containing the three tested analytes.